2005
DOI: 10.1186/1471-2318-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Foot pressure distribution during walking in young and old adults

Abstract: BackgroundMeasurement of foot pressure distribution (FPD) is clinically useful for evaluation of foot and gait pathologies. The effects of healthy aging on FPD during walking are not well known. This study evaluated FPD during normal walking in healthy young and elderly subjects.MethodsWe studied 9 young (30 ± 5.2 years), and 6 elderly subjects (68.7 ± 4.8 years). FPD was measured during normal walking speed using shoe insoles with 99 capacitive sensors. Measured parameters included gait phase characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
3
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(144 citation statements)
references
References 16 publications
4
113
3
10
Order By: Relevance
“…In addition, weight-bearing on the dominant side preferentially occurred on the medial surface and heel during normal walking. These findings are consistent with the results of Hessert et al who found that the forces needed to stabilize the ankle are increased in the medial and posterior foot of older adults during the heel touch phase 22) . The presence of the larger contact area during walking may indicate increased sway and decreased stability, and therefore, increased fall risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, weight-bearing on the dominant side preferentially occurred on the medial surface and heel during normal walking. These findings are consistent with the results of Hessert et al who found that the forces needed to stabilize the ankle are increased in the medial and posterior foot of older adults during the heel touch phase 22) . The presence of the larger contact area during walking may indicate increased sway and decreased stability, and therefore, increased fall risk.…”
Section: Discussionsupporting
confidence: 93%
“…We investigated differences in peak plantar pressure and contact surface area between the dominant and non-dominant sides because these measurements have been shown to be clinically useful in the diagnosis of fall risk, the treatment of gait disorders and falls, and the identification of anatomical foot deformities 21,22) . The peak pressures recorded were similar to those reported in previous studies of older adults 23) .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that elderly people bore more weight on the lateral side of the foot than young people during heel contact and push-off and that the higher lateral weight bearing may affect stability during gait 12) . Bryant and colleagues 23) studied the difference of FP in normal, hallux valgus, and hallux limitus feet.…”
Section: Discussionmentioning
confidence: 97%
“…The distribution and magnitude of plantar FP can provide useful information for diagnosing the various foot disorders [9][10][11] . Study of foot biomechanics reported that variation of plantar FP is useful for determining abnormal gait 12) . The measurement of plantar FP also provides useful objective information for clinicians such as physical therapists, assisting them with decisions over which treatment options should give the best clinical outcome 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Instrumented shoe insoles that do not interfere with walking (Pedar-X system, Novel, Munich, Germany) were used to record plantar pressures at 50 Hz. 16 Each insole was 2.5 mm thick and contained a matrix of 99 capacitive pressure sensors with a spatial resolution of 1.6-2.2 cm.…”
mentioning
confidence: 99%